Increased Neutrophil/Lymphocyte Ratio in Patients with Depression is Correlated with the Severity of Depression and Cardiovascular Risk Factors - SARI, İBRAHİM; SÜNBÜL, MURAT; YANARTAŞ, ÖMER (KOREAN NEUROPSYCHIATRIC ASSOC, 2016)
Objective Chronic inflammation is associated with cardiovascular (CV) risk factors and psychiatric disorders. The neutrophil to lymphocyte ratio (NLR) has been investigated as a new biomarker for systemic inflammatory response. The aim of the study is to investigate the relation of NLR with severity of depression and CV risk factors. Methods The study population consisted of 256 patients with depressive disorder. Patients were evaluated with the Hamilton Rating Scale for Depression (HAM-D). Patients were classified into four groups according to their HAM-D score such as mild, moderate, severe, and very severe depression. Patients were also evaluated in terms of CV risk factors. Results Patients with higher HAM-D score had significantly higher NLR levels compared to patients with lower HAM-D score. Correlation analysis revealed that severity of depression was associated with NLR in depressive patients (r=0.333, p<0.001). Patients with one or more CV risk factors have significantly higher NLR levels. Correlation analysis revealed that CV risk factors were associated with NLR in depressive patients (r=0.132, p=0.034). In logistic regression analyses, NLR levels were an independent predictor of severe or very severe depression (odds ratio: 3.02, 95% confidence interval: 1.867-4.884, p<0.001). A NLR of 1.57 or higher predicted severe or very severe depression with a sensitivity of 61.4% and specificity of 61.2%. Conclusion Higher HAM-D scores are associated with higher NLR levels in depressive patients. NLR more than 1.57 was an independent predictor of severe or very severe depression. A simple, cheap white blood cell count may give an idea about the severity of depression.
Keywords: Depression; Lymphocyte; Neutrophil; Inflammatory; Cardiovascular risk; CORONARY-ARTERY-DISEASE; C-REACTIVE PROTEIN; LYMPHOCYTE RATIO; INFLAMMATORY MARKERS; NEUTROPHIL; ASSOCIATION; MORTALITY; DISORDER; SCALE